Assessment of ecological quality status of Küçükçekmece Bay (Marmara Sea) by applying BENTIX, AMBI, BOPA and BO2A biotic indexes - CAGLAR, S.; ALBAYRAK, S. (Mediterranean Marine Science, 2012)
This study was carried out to explore the effectiveness of different biotic indexes in the Marmara Sea. The assessment of ecological quality status (EQS) was performed by applying the biotic indexes BENTIX, AMBI, BOPA, BO2A and Shannon-Wiener diversity, in combination with the estimation of total organic carbon (TOC) content of sediments. BOPA and BO2A indexes tended to overestimate the EQS of the stations. BENTIX was the most efficient index as it demonstrated conceivable EQS results with respect to TOC load and successfuly determined “acceptable” or “not acceptable” status of the stations. TOC content of sediment, which significantly correlated with several benthic measures (S, N, AMBI, BENTIX), proved to be a valuable proxy measure in evaluating the likelihood of benthic impairment. When overall EQS of northern Marmara Sea was discussed, the region was designated as ecologically disturbed with only 25.7% of the stations in acceptable status.